Hydrothermal synthesis and characterization of Bi2MoO 6 nanoplates and their photocatalytic activities - Anukorn Phuruangrat (2018)
The pH effect of the precursor solutions on the phase, morphologies, and photocatalytic activity of Bi 2 MoO 6 synthesized by a hydrothermal reaction at 180°C for 20 h was investigated. X-ray powder diffraction (XRD), Raman spectroscopy, Fourier transform infrared (FTIR) spectrometry, scanning electron microscopy (SEM), and transmission electron microscopy (TEM) revealed the presence of pure orthorhombic well-crystallized γ -Bi 2 MoO 6 nanoplates, including the symmetric (A 1g) and asymmetric (A 2u) stretching vibrations of the MoO 6 octahedrons involving the motion of apical oxygen atoms. The photocatalytic activity of Bi 2 MoO 6 nanoplates at the pH 6 determined via the decomposition of rhodamine-B (RhB) organic dye was the highest at 98.66% decolorization under Xe light irrad iation. © 2013 Anukorn Phuruangrat et al.